Intraoperative cholangiography in laparoscopic biliary surgery - Veirano, Gustavo; Bermúdez, Jorge; Morelli, Raúl (Cirugía del Uruguay, 1992)
The authors analyse the experience obtained on intraoperative cholangiography in the first 79 laparoscopic cholecystectomies carried out at the British Hospital. They describe the technique employed far its realizátion as we/1 as different possible variations. They discuss the controversy of its systematic or directed realization. They conclude that it should be carried out systematically when laparoscopic biliary surgery is in its initial period of apprenticeship in arder to: offer the patient al/ warranties as it is a new technique and acquire training in its laparoscopic realization even if it becomes of selective indica/ion in the future.